LEKATAN BAJA TULANGAN TERHADAP BETON PENGARUH PENAMBAHAN STYRENE BUTADIENE LATEX - Tumingan Tumingan (Universitas Lambung Mangkurat, 2009)
The characteristic of bond has influinced the structural integrity and behaviour of reinforced concrete, even the character of Latex Modified concrete (LMC) bond expected to increase the strength. Many researches have improved that some phenomenous happened to latex modified concrete (LMC). This report about some important phenomenons, such as : bond strength, bond stress, and splices. This bond strength and bond stress will be bond mechanism between concrete and steel reinforcement in reinforced concrete material is the main tool for transferring internal forces between concrete and reinforcement. In the study, a total of thirty-six cylinder concrete the 15-cm diameter and 30-cm height to bond specimens were tested. The parameter varied in the testing is three-bar diameter and two-types of bar (plain or deformed) to normal concrete and latex modified concrete. Result from the study have shown that plain bar from latex concrete to increase bond strength for 8,5%, from the bond strength normal concrete is 73.19 kg/cm2 to 79.41 kg/cm2 in latex modified concrete. That deformed bar to increase bond strength for 16,0% from the bond strength normal concrete is 87.02 kg/cm2 to 100.90 kg/cm2 in the latex concrete.